Fibrilasi Atrium pada Penyakit Paru Obtruktif Kronik - Silmi Kaffah; Yoga Yuniadi; Erlang Samoedro (Jurnal Kardiologi Indonesia, 2015)
Chronic Obstructive Pulmonary Disease (COPD) often coexists with cardiovasculae disease (comorbidities) that may have a significant impact in prognosis. Atrial fibrillation (AF) is the most common comorbid, which is supraventricular tachyarrhythmias uncoordinated and ineffective atrial activation. Emergence of atrial fibrillation if not handled properly associated with morbidity and mortality are high . Exact pathogenesis of AF in COPD but may associated with atrial factors , inflammation ,activation of the renin - angiotensin - aldosterone system (RAAS), coronary heart disease , disorders of the autonomic tone and pharmacological. Complications of AF consisted of thromboembolic events including stroke. The management of AF with COPD should be adjusted to optimize therapeutic result